Pelatihan Bahasa Inggris Berequivalent TOEFL Pada Reading Test CBT Terhadap Mahasiswa Semester Akhir Di Universitas Muhammadiyah dan IAIN Palangka Raya - A'am Rifaldi Khunaifi; Ilham Ilham; Bayu Suratmoko (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
English is an international language. In Indonesia, English is taught as a foreign language (English as a Foreign Language/EFL) from Elementary Schools to Higher Education. Especially at the University of Muhammadiyah Palangkaraya and IAIN Palangka Raya consider the importance of English which is shown through the TOEFL test and meet the scores determined before they are Judisium or Munakasah and have completed the thesis hearing in one semester. There were 20 participants from the Palangkaraya UM Students and Palangkaraya IAIN. The training method used in the English equivalent of Toefl training on Reading Tests is to use the Toefl training module on Reading Tests and also using a computerized software program in Toefl training on Reading Tests. The results of this training The training activities showed an increase between the pre-test and post-test results. The mean pre-test was 61 and the post-test mean increased to 83.6. In the pretest conducted to 20 participants were in the low category with a total of 4 people, a medium category of 13 people and a high of 3 people. The post-test results showed an increase in the score, namely the low category of 4 people, the medium category of 12 people and the high category increased to 4 people.